Penerimaan Guru Sekolah Dasar Terhadap Aplikasi SchoolShare: Analisis UTAUT - Teguh Trianung Djoko Susanto; Siti Zulaikha; Shinta Doriza; Evitha Soraya; Easyah Theoloni; Alfiya Farashati (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service (PkM) activity introduced SchoolShare, a web-based knowledge-sharing application for elementary school teachers in partner villages/regions, and evaluated its initial technology acceptance using an extended Unified Theory of Acceptance and Use of Technology (UTAUT) model with additional Attitude (ATT) and Willingness to Make Payment (WMP) constructs. The first training was held at SDN Rawamangun 05, East Jakarta, and a 23-item, 7-construct UTAUT questionnaire was distributed to 107 teachers after training. At this reporting stage, complete and analyzable data were available for three constructs only: Performance Expectancy (PE, 4 items), Behavioral Intention (BI, 3 items), and Willingness to Maintain/Purchase (WMP, 2 items); results reported here are therefore descriptive. All indicators had a median of 4 on a 1-5 scale. BI obtained the highest construct mean (4.022; SD=0.487), followed by WMP (4.009; SD=0.587) and PE (3.937; SD=0.424). The pattern of BI exceeding PE suggests relatively strong usage intention despite performance-benefit perceptions not yet being fully confirmed, a pattern common at the early piloting stage of technology implementation. Structural model testing (PLS-SEM) of 12 hypotheses (H1-H12) could not yet be conducted because data for the remaining constructs did not meet analysis requirements, and remains the main agenda for the next stage of the program.